Developing an Animal Model for Swenson Transanal Endorectal Pull-Through: A New Possibility for Training and Research Purposes - Gandra de Meira, Maria Luiza [UNESP]; Buraschi Antunes, Renata [UNESP]; de Oliveira Zani, Vitoria [UNESP]; Dutra de Oliveira, Gustavo [UNESP]; Generoso, Diego [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Lourenção, Pedro Luiz Toledo de Arruda [UNESP] (Taylor & Francis, 2024)
As far as we know, no report uses the Swenson transanal endorectal pull-through technique in an animal model. Our objective is to describe the use of this technique as an experimental model for training and research purposes. Ten Norfolk hybrid rabbits were randomly selected from our experimental laboratory, with a mean weight of 3539.3 (± 678.4) g. Neither colon preparation nor fast were used before the procedures. The surgical technique was based on the description performed by Levitt et al. (2013, J Pediatr Surg. 2013;48(11):2289–2295). Information related to the surgical procedures and the clinical evolution in the postoperative period were recorded and analyzed. There were no deaths or severe complications. The anesthetic and the surgical times were significantly higher for the first three animals of the experiment. Our animal model proved adequate to perform the transanal endorectal Swenson pull-through technique, allowing the training of surgical skills through a model similar to the human, with few anesthetic complications and good postoperative evolution, including postoperative follow-up. We believe that it will serve as a learning tool in many institutions that are continuously searching for improved new techniques and will support new researches in this area.
Keywords: endorectal pull through; experimental model; Hirschsprung disease; surgery; Swenson procedure